Morus alba L. : creating miles of smiles / Nurhayati Mohamad Zain … [et al.] - Mohamad Zain, Nurhayati; Mohd Amin, Indah; Ahmad, Vivi Noryati; Mohd Hairi, Nur Haleesa; Mahadzir, Noor Izzyani (2019)
The aims of the study are to determine the antimicrobial and antibiofilm activities of M. alba leaves extract against Streptococcus mutans (S.mutans). Method: The antimicrobial activity was evaluated using minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The antibiofilm potential of extract was evaluated using biofilm inhibition assay and biofilm eradication assay. Oradex mouthwash with 0.12% CHX was used as a positive control. All experiments were performed in triplicate and repeated four times independently. Data were analysed using SPSS software version 23. A Kruskal-Wallis test followed by post-hoc Mann-Whitney U test was applied and level of significance was set at P < 0.001. Results: Morus alba (M.alba) leaves extract showed antimicrobial activity against S.mutans with MIC and MBC, 25mg/ml and 50mg/ml respectively. The adherence of bacteria on extract treated surface (0.5x MIC) was significantly reduced with adherence inhibition percentage of 72.5% compared to positive control CHX 0.12% (63%). At 0.5x MIC concentration, the extract also disrupted preformed biofilms with eradication percentage of 52.87%. Conclusion: The results suggest that M. alba leaves extract represents an untapped source of local plant with antibiofilm activity against S.mutans that could be a resource in the development of therapeutic natural products in managing dental caries.